The importance of absorptive capacity towards innovation in small-medium enterprises: is human capital a moderating factor? - Mahir Pradana; Wahyuddin S. (Jurnal Sosioteknologi, 2020)
Previous literatures have reviewed that innovation ability relies on the capacity to absorp new knowledge (absorptive capacity). This study aims to examine the effect of absorptive capacity on innovation in the scope of small and medium enterprises (SMEs) in the province of West Java, Indonesia. To see whether human resource factors play a role in the ability of absorptive capacity, this study uses human capital as a mediator. The results of the study concluded that the scope of SMEs is different from multinational industries, where human capital apparently does not act as a mediator in the relationship between absorptive capacity and innovation.